Detailed Studies of Lencitular Galaxies in the Local Universe - Buzzo, Maria Luisa Gomes (2020)
S0 galaxies are supposedly a transitional stage in the life of a galaxy, in which it shares properties of both elliptical and spiral galaxies. Thus, understanding this type of object can bring important information on the whole field of galaxy evolution. Lenticular galaxies account for almost half of the giant galaxy population in the nearby universe, yet their formation history and whether they are a unique or a composite class of objects remain an open question of modern astronomy. In this work, we study this class of galaxies in three fronts using different datasets: firstly, we look at a fully formed lenticular galaxy, NGC 3115, using multi-wavelength data to recover its formation history and evolution; secondly, we look at an event that could generate an S0, the major merger NGC 1487, using MUSE/VLT integral field spectroscopy (IFS) data. Finally, we study the distribution of S0 galaxies in the local universe using photometric data from the S-PLUS survey. Putting together these three works, we aim at providing a better understanding of lenticular galaxies in the local universe and at identifying what are the progenitors and the most likely formation scenarios in different environments. In the Hubble classification scheme, lenticular galaxies are defined to have a disk, without spiral arms. Yet a more detailed study reveals that lenticulars present several subcomponents, as a disk, a bulge, and in some cases also a bar and lenses. Decomposing a galaxy in its components allows recovering the colour gradients present in the system, its star formation history and, finally, its assembly history. We used GALFITM to perform a multi-wavelength structural decomposition of the closest lenticular galaxy to the MW, NGC 3115, resulting in the description of its stellar populations into three main components, including a bulge, a thin disk and a thick disk. We recovered pixelized color-magnitude diagrams and the spectral energy distribution of the components. The results show that the majority of the mass of the galaxy is in the bulge region and that this is the bluest component, suggesting both active galactic nuclei (AGN) activity and recent star formation events. We show that this galaxy holds a bar and central spiral-like features, probably created during a recent interaction. Finally, we propose a scenario for the formation of NGC 3115 based on an initial gas-rich merger, followed by a sequence of accretions and AGN feedback, responsible for quenching the galaxy, until a recent encounter reignited the star formation in the bulge and generated the observed spiral features. It is well known that S0 galaxies can be formed by different processes, here we study the effectiveness of major mergers as one of the formation mechanisms of S0 galaxies. Using MUSE/VLT IFU data of the major merger NGC 1487, we study the physical and kinematical properties of the system. We find an inversion in the metallicity gradient of the system NGC1487, explained by metal mixing processes. The velocity field revealed a rotating pattern in one of the sub-components of NGC1487, showing that the galaxy may be in the process of recreating a disc. We conclude that if the evolution of the system would lead to the formation of a disc, then this merger event could evolve passively to become an S0 galaxy in several Gyr from now. Finally, to understand the distribution of lenticular galaxies in the local universe, and the role of environments in their formation, we determined photometric redshifts and spectral types for galaxies in the S-PLUS survey. We identified the objects best-fitted by the lenticular galaxies template and found their distribution across the local universe. The results show that S0s mostly lie in clustered regions and are hardly isolated. Moreover, we show that among galaxies identified as lenticular according to their spectral-type, the ones with low star formation rates also present a visual morphology typical of lenticular galaxies, while those with high star formation rates are probably lenticular galaxies with nuclear activity or incorrectly classified spiral galaxies.